Revising the taxonomic status and distribution of the Paracalanus parvus species complex (Copepoda, Calanoida) in the Mediterranean and Black Seas through an integrated analysis of morphology and molecular taxonomy. - Kasapidis, P., I. Siokou, M. Khelifi-Touhami, M.G. Mazzocchi, M. Matthaiaki, E. Christou, M.L.F. De Puelles, A. Gubanova, I. Di Capua, S. Batziakas & C. Frangoulis (Journal Of Plankton Research, 2018)
The marine copepod Paracalanus parvus has long been considered the most abundant representative of the genus and one of the main components of coastal zooplankton in the Mediterranean and Black Seas. However, subtle morphological differences between P. parvus, P. indicus and P. quasimodo hamper correct taxonomic identiﬁcation. To clarify the taxonomic status and distribution of this species complex in the Mediterranean and Black Seas, DNA barcoding as well as an integrated morphological and molecular analysis was conducted on samples collected across these two basins. DNA barcoding conﬁrmed the presence of P. parvus s.s. in the Black Sea and revealed four Paracalanus species in the Mediterranean Sea, including the morphologically undescribed Paracalanus sp. F. The most abundant species in all coastal areas was P. quasimodo, while P. parvus s.s. was conﬁned to areas of the northern Mediterranean Sea. The phylogeographic analysis indicated that the boreal species P. parvus s.s. has a relic distribution in the Mediterranean and may have been displaced by the subtropical P. quasimodo during the last interglacial period. The integrated analysis revealed inconsistencies between morphological and molecular taxonomic identiﬁcation and indicated that the taxonomic characters traditionally used are not adequate to discriminate between these species.